GC Analysis of Essential Oils, TLC Profiling of Pigments and DNA Extraction from Eucalyptus Species - Rupal Singh1, Noor Afshan Khan2, Abin Mani1, Jaswant Patel1, Sadaf Quereshi1*, Ankita Upadhyay1, (Current Botany, 2011)
Medicinal plants, herbs, spices & herbal remedies are integral components of alternative system of medicine since times immemorial. Eucalyptus essential oils are highly valued in therapeutic and pharmaceutical preparations because of their main component 1, 8-cineole. In this study, extraction of essential oils from three different varieties of Eucalyptus species viz. E. saligna,Ã‚Â E. tereticornis and E. tetragona were carried out with oil yield of 2.0%, 1.0% and 1.5%, respectively, along with their GC analysis. Major peaks from GC study indicate the presence of important constituents. TLC analysis of leaf pigments represents the most important pigments followed by DNA extraction and purification which reveal spectrophotometric data of DNA concentration-250ng/Ã‚Âµl (E. saligna), 220ng/Ã‚Âµl (E. tereticornis) and 200ng/Ã‚Âµl (E. tetragona).